Optimization in reliability based design of laminated composite structures - C. A. C. Antonio (1993)
Design of laminated composite structures is made using rules based onservice stresses criteria. The replacement of these criteria by guidelinessupported by failure modes rules will contribute to a more accurate design. Thisdesign enhancement is performed at the element and at the system levels. Toapply the reliability theory it was necessary to perform a statistical analysis oftest results concerning relevant material properties.The optimization of the structure weight was performed using a two levelsmethod. The types of structures studied were plates and shells using the layersangles and the layers thicknesses as design variables. Besides the safetyconstraints, based on material properties randomness, upper limits wereimposed on global displacements. The strategy for the first level was tomaximize the material efficiency and that of the second level was to reduce thelayers thicknesses.The balanced solution between weight reduction and derivedstructural safety was tested on a plate and results were analysed and discussed.